Efektivitas Bimbingan Pra-Nikah oleh KUA Kecamatan Medan Tembung dalam Mencegah Perceraian di Kalangan Pasangan Muda - Riska Fatiah; Martuani Siregar (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
Pre-marriage counseling is a mandatory step that must be undertaken by prospective brides and grooms before the marriage contract, aimed at preparing them for married life. This study aims to identify and assess the effectiveness of the pre-marriage counseling program conducted by the Religious Affairs Office (KUA) of Medan Tembung District in reducing divorce rates in 2024. This study evaluates the effectiveness of pre-marriage counseling through five indicators: efficiency, adequacy, equity, responsiveness, and accuracy. The research employs a descriptive method with a qualitative approach, using data collection techniques such as observation, interviews, and documentation. The findings indicate that the pre-marriage counseling conducted by KUA Medan Tembung has been effective in reducing the divorce rate. This is due to the requirement for prospective couples to attend pre-marriage counseling before the marriage contract. The program has proven to be very helpful in preparing couples for married life, thus reducing the potential for divorce. The main objective of the pre-marriage counseling program implemented by KUA Medan Tembung is to prevent divorce among young couples in the district.